Design and development of network intrusion detection system detection scheme on network processing unit - Robin Salim,; Krishna Rao, G. S. V. R. (IEEE Xplore, 2006)
Network Intrusion Detection System (NIDS) is a significant system for information network infrastructure. Its primary goal is to detect possible network intrusion preferably in real-time by observing network traffic. With the constant increase of network speed and packets load, NIDS faces tremendous challenges for capturing packets and performing intrusion analysis in real-time. This paper proposes a design concept for signature-based NEDS using Network Processing Unit (NPU).